Seasonal changes in habitat use of White-fronted Geese near Antwerp, Belgium - Ysebaert, Tom J; Meire, Patrick M; Dhondt, Andr A (Wildfowl, 1988)
Distribution and habitat use of European White-fronted Goose Anser albifrons albifrons in winter were studied in relation to habitat selection near Antwerp (Belgium). Geese were counted on average three times a week. The vegetation was analysed in 78 plots, placed at random. Eight vegetation subgroups were distinguished, based on a TWINSPAN program. Goose usage was determined by counting droppings in the plots in 7 periods throughout the winter. Geese shifted from the study area towards the surrounding polder during cold spells. Geese also showed a temporal and spatial preference for distinct vegetation subgroups within the study area. Moreover, there are indications that they shifted feeding sites sequentially during winter. The different use of feeding sites was explained by the fact that the geese probably had to deal with finite food supplies of different qualities, and often with severe weather conditions and disturbance.